A Community Atmosphere Model With Superparameterized Clouds. (18th June 2013) - Randall, David; Branson, Mark; Wang, Minghuai; Ghan, Steven; Craig, Cheryl; Gettelman, Andrew; Edwards, James
Abstract : Simulations by climate models are used to project the climate change expected as atmospheric greenhouse gas concentrations rise. How much will the Earth warm? Will south Asia experience stronger monsoons in the future? Will the American Southwest continue to desiccate? How soon will the Arctic become ice free? How fast and how much will sea level rise? Climate models rely on the idea that sound physical principles can be used to translate basic information, such as emissions of carbon dioxide and aerosols, into changes in the energy balance that influence the formation of clouds, which over time play a key role in shaping future climate response to the emissions.